N-formyl-perosamine surface homopolysaccharides hinder the recognition of Brucella abortus by mouse neutrophils - Mora-Cartín, Ricardo (2016)
Brucella abortus is an intracellular pathogen of monocytes, macrophages, dendritic cells, and placental trophoblasts. This bacterium causes a chronic disease in bovines and in humans. In these hosts, the bacterium also invades neutrophils; however, it fails to replicate and just resists the killing action of these leukocytes without inducing significant activation or neutrophilia. Moreover, B. abortus causes the premature cell death of human neutrophils. In the murine model, the bacterium is found within macrophages and dendritic cells at early times of infection but seldom in neutrophils. Based on this observation, we explored the interaction of mouse neutrophils with B. abortus. In contrast to human, dog, and bovine neutrophils, naive mouse neutrophils fail to recognize smooth B. abortus bacteria at early stages of infection. Murine normal serum components do not opsonize smooth Brucella strains, and neutrophil phagocytosis is achieved only after the appearance of antibodies. Alternatively, mouse normal serum is capable of opsonizing rough Brucella mutants. Despite this, neutrophils still fail to kill Brucella, and the bacterium induces cell death of murine leukocytes. In addition, mouse serum does not opsonize Yersinia enterocolitica O:9, a bacterium displaying the same surface polysaccharide antigen as smooth B. abortus. Therefore, the lack of murine serum opsonization and absence of murine neutrophil recognition are specific, and the molecules responsible for the Brucella camouflage are N-formyl-perosamine surface homopolysaccharides. Although the mouse is a valuable model for understanding the immunobiology of brucellosis, direct extrapolation from one animal system to another has to be undertaken with caution. © 2016, American Society for Microbiology.